1995
DOI: 10.1074/jbc.270.44.26063
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Channel Expression with the Tandem Construct of α6-β2 GABAA Receptor Subunit Requires a Monomeric Subunit of α6 or γ2

Abstract: Despite the presence of the multiple subunits (␣, ␤, ␥, and ␦) and their isoforms for ␥-aminobutyric acid, type A (GABA A ) receptors in mammalian brains, the ␣x␤2␥2 subtypes appear to be the prototype GABA A receptors sharing many properties with native neuronal receptors. In order to gain insight into their subunit stoichiometry and orientation, we prepared a tandem construct of the ␣6 and ␤2 subunit cDNAs where the carboxyl-terminal of ␣6 is linked to the amino-terminal of ␤2 via a linker encoding 10 glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 23 publications
(26 reference statements)
2
74
0
1
Order By: Relevance
“…In contrast, in αβ-expressing receptors, desensitization was more significantly enhanced when F was present in the β subunit. There continues to be some debate regarding the stoichiometry of αβ-expressing receptors [1,2,5,7,11]. Although not definitive, our studies support the presence of 3 β and 2 α subunits in these receptors, since desensitization was more significantly enhanced in α1β2(T6′F) receptors compared to α1(T6′F)β2 receptors.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, in αβ-expressing receptors, desensitization was more significantly enhanced when F was present in the β subunit. There continues to be some debate regarding the stoichiometry of αβ-expressing receptors [1,2,5,7,11]. Although not definitive, our studies support the presence of 3 β and 2 α subunits in these receptors, since desensitization was more significantly enhanced in α1β2(T6′F) receptors compared to α1(T6′F)β2 receptors.…”
Section: Discussionsupporting
confidence: 65%
“…The most common GABA A R subunit combination found in the brain contains two ␣ subunits, two ␤ subunits, and one ␥ subunit (Im et al, 1995;Chang et al, 1996;Li and De Blas, 1997;Jechlinger et al, 1998;Farrar et al, 1999), although combinations of two ␣, one ␤, and two ␥ subunits also occur in the brain (Backus et al, 1993;Khan et al, 1994aKhan et al, ,b, 1996.…”
Section: Individual Hippocampal Pyramidal Cells and Interneurons In Cmentioning
confidence: 99%
“…In addition, Im et al (1995), using tandem constructs of ␣6-␤2 GABA subunits, concluded that ␣6␤2␥2 GABA receptors contain two ␣ subunits, two ␤ subunits, and one ␥ subunit.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%